PENERAPAN METODE KISAH ISLAMI UNTUK MENINGKATKAN PERILAKU AKHLAKUL KARIMAH ANAK DI TK IT RAUDHATUL JANNAH SALAM BUKU KABUPATEN MERANGIN - Sutiyana Sutiyana; Atika Wirdasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve children's noble character behavior through the implementation of the Islamic storytelling method at TK IT Raudhatul Jannah Salam Buku, Merangin Regency. The study was grounded in the importance of developing religious values and moral conduct in early childhood, particularly greeting, polite speech, praying, sharing, waiting patiently, and saying sorry and thank you. This study employed classroom action research based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The subject in this draft involved 15 group B children. Data were collected through observation, interviews, and documentation. The observation instrument consisted of six indicators of noble character behavior measured using four developmental categories: undeveloped, beginning to develop, developing as expected, and very well developed. The data were analyzed using descriptive quantitative percentages and qualitative field notes. The findings indicate that children's noble character behavior increased from 51.67% in the pre-cycle to 68.61% in cycle I and 83.89% in cycle II. The number of children who achieved the developing as expected and very well developed categories increased from 5 children (33.33%) in the pre-cycle to 9 children (60.00%) in cycle I and 13 children (86.67%) in cycle II. These findings suggest that Islamic storytelling combined with questioning, role modeling, habituation, picture/puppet media, and positive reinforcement can improve noble character behavior among early childhood learners.